Synthesis of ganoderic acid analogues to investigate their activity as anti-prostate cancer agents - Al-Obaidi, Mohammed (2019)
Cancers are one of the leading causes of premature human death globally. Prostate cancer is the second most common cancer in the world; chemoprevention can help decrease the proportion of fatal cases and prevent recurrence of the cancer. Ganoderic acids (GAs) are a type of C30 lanostane triterpenoid produced by the mushroom Ganoderma lucidum. Analogues of GAs which have previously been tested showed biological activity as anti-cancer compounds. In this project, the synthesis of new ganoderic acid DM (GA-DM) analogues starting from lanosterol is reported as well as a preliminary evaluation of their biological activity as anti-prostate cancer agents. Lanosterol is a cheap natural starting material from sheep wool grease that is commercially available in 50-60% purity. From literature data, the sites that may enhance the biological activity of lanosterol and are modified in this study are: C3, C7, and C24. This study outlines how aldehyde (10S,13R,14R,17R)-4,4,10,13,14-pentamethyl-17-((R)-5-oxopentan-2-yl)-2,3,4,5,6,7,10,11,12,13,14, 15,16,17-tetradecahydro-1H-cyclopenta[a]phenanthren-3-yl acetate was synthesised by Sharpless epoxidation of the C24/C25 double bond followed by oxidative cleavage. A series of molecules were then synthesized starting from this aldehyde intermediate including amines; azides; triazoles; lower homologues (olefin; diol and aldehyde) and GA-DM analogues. The compounds were found to be insoluble in DMSO, therefore alternative solvent options were investigated. A significant number of the compounds showed good solubility and low cancer cell line toxicity in ethyl acetate. The cytotoxicity of the ethyl acetate soluble compounds was evaluated against the PC3 and DU145 prostate cancer cell lines to assess their potential as anti-cancer drugs using MTT assay. Putting an acetate at C3 was found to greatly improve solubility and biological activity, whereas having a hydroxyl at C3 reduced both solubility and biological activity. The most effective compounds had values in the IC50 range 3-32 µM compared with methyl ganoderic acid-DM and ganoderic acid-DM with IC50 values of 0.3 and 40 µM respectively.